Analysis of the effect of Customer Value and Service Quality on Customer Satisfaction at PT Tera Logistik Indonesia Semarang Branch - Prima - Yoza; Noor - Suroija; Sri - Wahyuni (JOBS (Jurnal Of Business Studies), 2020)
The title of this research is The Effect of Customer Value and Service Quality on Customer Satisfaction at PT Tera Logistik Indonesia Semarang Branch.  PT Tera Logistik Indonesia Semarang branch is one of 57 ship agency companies  in Semarang, Central Java (inaportnet.dephub.go.id).  This condition make the company to compete for customer. As a company engaged in service sector, the compatition is competing to provide satisfactory services to consumer.  At PT Tera Logistik Indonesia there was a decrease in the number of service usage in 2019, the decrease in the number of customers was inseparable from the quality of service and value provided by the company to customers. The purpose of this study was to analyze the effect of customer value and service quality on customer satisfaction at PT Tera Logistik Indonesia Semarang branch. This study used a saturated sampling technique, with a sample size of 39 customers. The analysis technique used is multiple linear regression and classical assumption test. The results of this study indicate that partially, customer value has a significant effect on customer satisfaction and service quality has a significant effect on customer satisfaction. And simultaneously the variables of customer value and service quality have a significant and positive effect on customer satisfaction with an influence contribution of 53.7%. This shows that PT Tera Logistik Indonesia Semarang Branch has to pay attention of  satisfaction from customers needs to increasing customer value and the quality service that  provided to customers.